2002
DOI: 10.1152/ajpgi.00196.2001
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor reduces the development of necrotizing enterocolitis in a neonatal rat model

Abstract: Necrotizing enterocolitis (NEC) is the most common gastrointestinal disease of prematurely born infants. Maternal milk plays an important protective role against NEC development and is the major source of epidermal growth factor (EGF) for neonates. The aim of this study was to examine the effect of orally administered EGF on the incidence of NEC in a neonatal rat model. Newborn rats were artificially fed either with growth factor-free rat milk substitute (RMS) or RMS supplemented with 500 ng/ml of EGF (RMS+EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
235
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(253 citation statements)
references
References 57 publications
11
235
1
4
Order By: Relevance
“…Hypothermia and hypoxia cause a redirection of blood away from the intestine and colon to more vital organs, such as the heart, liver, brain, and adrenal glands (2). The resulting hypoxia/reoxygenation-induced ischemia/reperfusion of the intestine has been related to an increased prevalence of gut dysfunction (1) and is the basis of several animal models of NEC (6,13,21). In the present study, despite CS pigs experiencing a period of hypothermia and impaired respiratory function, the incidence and severity of NEC did not differ between CS and VD pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia and hypoxia cause a redirection of blood away from the intestine and colon to more vital organs, such as the heart, liver, brain, and adrenal glands (2). The resulting hypoxia/reoxygenation-induced ischemia/reperfusion of the intestine has been related to an increased prevalence of gut dysfunction (1) and is the basis of several animal models of NEC (6,13,21). In the present study, despite CS pigs experiencing a period of hypothermia and impaired respiratory function, the incidence and severity of NEC did not differ between CS and VD pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to induce NEC in several animal models by exposing term neonates to hypoxia and cold stress (1,13) has fostered speculation that deficiencies in thermoregulation and respiratory capabilities, which are common for preterm infants (3), increase the risk of NEC. If so, the thermoregulatory and respiratory problems that are more common among infants delivered by cesarean section (CS), compared with those born vaginally (VD) (3,39), may be a determinant of NEC risk.…”
mentioning
confidence: 99%
“…Animals were hand fed six times daily with a total volume of 850 l of rat milk substitute/day (23). Experimental NEC was induced by asphyxia (breathing 100% nitrogen gas for 60 s) and cold stress (4°C for 10 min) twice daily (11). Neonatal rats were divided into the following experimental groups: hand fed with formula (NEC; n ϭ 30); hand fed with formula containing 5 ϫ 10 6 colony-forming units (CFU) of B. bifidum OLB6378 in two feedings per day (NEC ϩ B. bifidum; n ϭ 30); and dam fed littermates fed by surrogate mothers as a baseline control (DF, n ϭ 16).…”
Section: Animal Modelmentioning
confidence: 99%
“…Breast milk contains several growth factors that are known to promote epithelial survival such as epidermal growth factor (EGF) [84], heparinbinding EGF-like growth factor (hb-EGF) [85], hepatocyte growth factor (HGF) [86], insulin-like growth factor (IGF) [87], transforming growth factor-beta (TGF-β) [88], erythropoietin [89] and vascular endothelial growth factor (VEGF) [90]. Several of these factors have recently been found to be potentially protective against development of NEC when given as formula supplementation in animal studies [79,91] and all of these growth factors have been shown to promote enterocyte survival either in vivo or in vitro [78,86,[92][93][94][95]. Commercial formulas are devoid of these growth factors and, therefore, enterocytes of formula-fed infants are deprived of the exogenous supplementation of trophic and survival signals imparted by these molecules.…”
Section: Growth Factors and Necmentioning
confidence: 99%